2009
DOI: 10.1128/jvi.01434-08
|View full text |Cite
|
Sign up to set email alerts
|

Association of Increased Pathogenicity of Asian H5N1 Highly Pathogenic Avian Influenza Viruses in Chickens with Highly Efficient Viral Replication Accompanied by Early Destruction of Innate Immune Responses

Abstract: The Asian H5N1 highly pathogenic avian influenza (HPAI) viruses have been increasing in pathogenicity in diverse avian species since 1996 and are now widespread in Asian, European, and African countries. To better understand the basis of the increased pathogenicity of recent Asian H5N1 HPAI viruses in chickens, we compared the fevers and mean death times (MDTs) of chickens infected with the Asian H5N1 A/chicken/Yamaguchi/7/04 (CkYM7) strain with those infected with the H5N1 Duck/Yokohama/aq10/03 (DkYK10) strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
124
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 60 publications
(104 reference statements)
7
124
0
2
Order By: Relevance
“…Other literature suggests that suppression of the cytokine response alone may not be sufficient to provide adequate protection, as has been noted in mice infected with human H5N1 isolates (41). On the other hand, however, there is clear evidence of hypercytokinemia in H5N1-and H7N9-infected humans (5-7) and chickens (39). Moreover, functional microarray analysis of lung samples obtained from infected ferrets has shown overexpression of genes involved in IFN signaling, especially CXCL10 (42).…”
Section: Discussionmentioning
confidence: 99%
“…Other literature suggests that suppression of the cytokine response alone may not be sufficient to provide adequate protection, as has been noted in mice infected with human H5N1 isolates (41). On the other hand, however, there is clear evidence of hypercytokinemia in H5N1-and H7N9-infected humans (5-7) and chickens (39). Moreover, functional microarray analysis of lung samples obtained from infected ferrets has shown overexpression of genes involved in IFN signaling, especially CXCL10 (42).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, infection caused a decrease in the expression of IFN-γ in chicken PBMC. Similarly, Suzuki et al [18] found that IFN-γ decreased in the lung of chicken infected with HPAIV A/chicken/Yamaguchi/7/2004 (H5N1). Both this virus and the virus used in our study were isolated in Asia in recent years.…”
Section: Discussionmentioning
confidence: 83%
“…Both this virus and the virus used in our study were isolated in Asia in recent years. These recent Asian H5N1 viruses are thought to cause early destruction of the innate immune response in chicken [18], and have been increasing in pathogenicity in diverse avian species. On the other hand, in quail PBMC, the increase of IFN-γ expression appears to have activated the antiviral function in the innate immune response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations